2017
DOI: 10.1109/tie.2017.2682787
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Efficiency and Lifetime of a Proton Exchange Membrane Fuel Cell Using Nonlinear Model-Predictive Control With Nonlinear Observation

Abstract: The aim of this research is to develop and test in a simulation environment an advanced model-based control solution for a Proton Exchange Membrane Fuel Cell (PEMFC) system. A Nonlinear Model Predictive Control (NMPC) strategy is proposed to maximise the active catalytic surface area at the Cathode Catalyst Layer (CCL) to increase the available reaction area of the stack and to avoid starvation at the catalyst sites. The PEMFC stack model includes a spatial discretisation that permits the control strategy to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…This strategy showed improved results in comparison with a fixed stoichiometry control strategy for the fuel cell. An NMPC strategy that ensures maximum efficiency of an LT-PEMFC power system by maximizing the electrochemically active surface area is proposed in [6]. To guarantee lifetime enhancement of the LT-PEMFC, the designed controller imposes operational constraints to avoid hydrogen and oxygen starvation at the anode and cathode compartments, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy showed improved results in comparison with a fixed stoichiometry control strategy for the fuel cell. An NMPC strategy that ensures maximum efficiency of an LT-PEMFC power system by maximizing the electrochemically active surface area is proposed in [6]. To guarantee lifetime enhancement of the LT-PEMFC, the designed controller imposes operational constraints to avoid hydrogen and oxygen starvation at the anode and cathode compartments, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of this study, the control of the fuel cell subject to a dynamic drive cycle is of much greater practical relevance. Various test scenarios have recently been reported which rely on the New European Driving Cycle (NEDC) as the validation drive cycle for the control of a fuel cell vehicle [13][14][15]. The Worldwide Harmonised Light Vehicles Test Procedure (WLTP) also developed in 2015 has been used as the validation drive cycle for several studies concerning fuel cell control [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…New technological advancements to increase fuel cell durability have been achieved in the field of materials and catalysts [5]. Researchers are proposing advanced control techniques to improve the performance of fuel cells as well as improve their life expectancy [6]. For example, it has been demonstrated that the internal conditions of the fuel cell (i.e.…”
Section: Introductionmentioning
confidence: 99%